Selected Examples of Radiohm Resistivity Surveys for Geotechnical Exploration. - Hoekstra,P; Sellmann ,P V; Delaney,A J (1977)
Measurements of ground resistivity using radio wave techniques have been made in support of several geotechnical projects. Examples of surveys conducted for locating and evaluating gravel deposits, for delineating permafrost, and for extrapolating subsurface information between drill holes are used to illustrate some advantages of ground and airborne surveys using this method. (Author)